Chapter Ethics in Educational Reserch - Torlone, Francesca (Studies on Adult Learning and Education, 2023)
The ethical dimension of research in adult education is deeply connected to the real, substantial quality of research. The ethical dimension of adult education research, mostly neglected, is analysed from an epistemological perspective. We assume that ethical conduct of educational research is more complex than adhering to a set of rules and procedures as it has to deal with the meaning and purpose of adult education research, the distribution of pedagogical powers and the control over them to put individual and collective answers in practice.